2018
DOI: 10.1042/cs20171634
|View full text |Cite
|
Sign up to set email alerts
|

The pericyte–glia interface at the blood–brain barrier

Abstract: The cerebrovasculature is a multicellular structure with varying rheological and permeability properties. The outer wall of the brain capillary endothelium is enclosed by pericytes and astrocyte end feet, anatomically assembled to guarantee barrier functions. We, here, focus on the pericyte modifications occurring in disease conditions, reviewing evidence supporting the interplay amongst pericytes, the endothelium, and glial cells in health and pathology. Deconstruction and reactivity of pericytes and glial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 165 publications
1
54
0
Order By: Relevance
“…Electron microscopy studies showed increased pinocytotic activity, tight junction aberration and a thickening of the basement membrane in epileptic brains [28,29]. In addition to pinocytosis, pericyte-microglia clustering was observed in the epileptic brain, and likely contributes to BBB dysfunction [30,31]. Furthermore, astrocytes undergo morphological and functional alterations after insults and in the epileptic brain.…”
Section: Bbb Structural Alterations In Epilepsymentioning
confidence: 99%
“…Electron microscopy studies showed increased pinocytotic activity, tight junction aberration and a thickening of the basement membrane in epileptic brains [28,29]. In addition to pinocytosis, pericyte-microglia clustering was observed in the epileptic brain, and likely contributes to BBB dysfunction [30,31]. Furthermore, astrocytes undergo morphological and functional alterations after insults and in the epileptic brain.…”
Section: Bbb Structural Alterations In Epilepsymentioning
confidence: 99%
“…Despite the implication of the cerebrovasculature in epilepsy, the cellular changes occurring at the outer wall of the BBB remain to be fully defined. Under physiologic conditions, a precise structural arrangement outlines the contact between mural cells and astrocytic end‐feet at the brain endothelium . We previously reported that in response to status epilepticus (SE) and during epileptogenesis, cerebrovascular pericytes or smooth muscle cells undergo redistribution and remodeling, potentially contributing to BBB permeability .…”
Section: Introductionmentioning
confidence: 99%
“…Under physiologic conditions, a precise structural arrangement outlines the contact between mural cells and astrocytic end-feet at the brain endothelium. 5,6 We previously reported that in response to status epilepticus (SE) and during epileptogenesis, cerebrovascular pericytes or smooth muscle cells undergo redistribution and remodeling, potentially contributing to BBB permeability. [7][8][9] During seizures, pericyte damage negatively impacts neurovascular coupling.…”
Section: Introductionmentioning
confidence: 99%
“…The BBB consists of a multicellular assembly of endothelial cells, astrocytes, and pericytes, 30 with a main function of separating the circulating blood solutes and cells from the ISF and the brain parenchyma. The BBB consists of a multicellular assembly of endothelial cells, astrocytes, and pericytes, 30 with a main function of separating the circulating blood solutes and cells from the ISF and the brain parenchyma.…”
Section: Macromolecule Accumulation and Neuronal Hyperexcitabilitymentioning
confidence: 99%
“…The blood-brain barrier (BBB) is a functional-anatomic unit and a fundamental segment of the cerebrovascular tree. The BBB consists of a multicellular assembly of endothelial cells, astrocytes, and pericytes, 30 with a main function of separating the circulating blood solutes and cells from the ISF and the brain parenchyma. 31 BBB damage and dysfunction play an important role in generating and sustaining ictal activity.…”
Section: Blood-brain Barrier Impairment Macromolecule Accumulationmentioning
confidence: 99%